Grower Expectations of New Technologies for Applications in Precision Horticulture - Reza Ehsani; Sindhuja Sankaran; Cristian Dima (EDIS)
AE467, a 4-page article by Reza Ehsani, Sindhuja Sankaran, and Cristian Dima, reports the results of a needs assessment focus meeting. It provides a synopsis of perceived apple and orange growers’ needs, expectations, and concerns related to the new technologies being developed for various precision horticulture applications. Published by the UF Department of Agricultural and Biological Engineering, October 2010.